Beispiel Nr: 17
$ \text{Gegeben:} \\ a1 \cdot x +b1 \cdot y =c1\\ a2 \cdot x +b2 \cdot y =c2 \\ \\ \text{Gesucht:} \\\text{x und y} \\ \\ \textbf{Gegeben:} \\ \\ -\frac{1}{2} x +4 y =6\\ -2 x -8 y = 2 \\ \\ \\ \\ \textbf{Rechnung:} \\\begin{array}{l|l} \begin{array}{l} I \qquad -\frac{1}{2} x +4 y =6\\ II \qquad -2 x -8 y = 2 \\ \text{I nach y auflösen}\\ -\frac{1}{2} x +4 y =6 \\ -\frac{1}{2} x +4 y =6 \qquad /+\frac{1}{2} x\\ 4 y =6 +\frac{1}{2} x \qquad /:4 \\ y =1\frac{1}{2} +\frac{1}{8} x \\ \text{II nach y auflösen}\\ -2 x -8 y =2 \\ -2 x -8 y =2 \qquad /+2 x\\ -8 y =2 +2 x \qquad /:\left(-8\right) \\ y =-\frac{1}{4} -\frac{1}{4} x \\ \text{I = II}\\ 1\frac{1}{2} +\frac{1}{8} x =-\frac{1}{4} -\frac{1}{4} x \qquad /-\frac{1}{8} x /+\frac{1}{4} \\ 1\frac{1}{2}+\frac{1}{4} =-\frac{1}{4} x -\frac{1}{8} x \\ 1\frac{3}{4} =-\frac{3}{8} x \qquad /:\left(-\frac{3}{8}\right) \\ x=-4\frac{2}{3} \\ \text{x in I}\\ y =1\frac{1}{2} +\frac{1}{8} \cdot -4\frac{2}{3} \\ y=\frac{11}{12} \\ L=\{-4\frac{2}{3}/\frac{11}{12}\} \end{array} & \begin{array}{l} I \qquad -\frac{1}{2} x +4 y =6\\ II \qquad -2 x -8 y = 2 \\ \text{I nach x auflösen}\\ -\frac{1}{2} x +4 y =6 \\ -\frac{1}{2} x +4 y =6 \qquad /-4 y\\ -\frac{1}{2} x =6 -4 y \qquad /:\left(-\frac{1}{2}\right) \\ x =-12 +8 y \\ \text{II nach x auflösen}\\ -2 x -8 y =2 \\ -2 x -8 y =2 \qquad /+8 y\\ -2 x =2 +8 y \qquad /:\left(-2\right) \\ x =-1 -4 y \\ \text{I = II}\\ -12 +8 y =-1 -4 y \qquad /-8 y /+1 \\ -12+1 =-4 y -8 y \\ -11 =-12 y \qquad /:\left(-12\right) \\ y=\frac{11}{12} \\ \text{y in I}\\ x =-12 +8 \cdot \frac{11}{12} \\ x=-4\frac{2}{3} \\ L=\{-4\frac{2}{3}/\frac{11}{12}\} \end{array} \end{array} $